A Fuzzy Logic Based Approach to Solve Interval Multiobjective Nonlinear Transportation Problem - Dalman, Hasan; Sivri, Mustafa (NATL ACAD SCIENCES INDIA, 2019)
This paper presents the solution procedure of multiobjective nonlinear transportation problem (MNOTP) where the cost coefficients of the objective functions, and the supply and the unknown demand parameters have been formulated as interval numbers by the decision maker. This problem has been converted into a conventional MNOTP where to minimize the interval nonlinear objective functions, the order relations that define the choice between intervals have been determined by the interval arithmetic. Also, the constraints with interval supply and unknown demand parameters have been transformed into its deterministic forms. Then the deterministic problems have been solved by two compromise programming methods. Finally, a numerical example is presented to illustrate the efficiency of the proposed procedure as well.
Keywords: Fuzzy programming; Interval numbers; Transportation problem; Multiobjective programming; Nonlinear programming; Science & Technology - Other Topics